On Dual k -Pell Quaternions and Octonions - Catarino, Paula (2017)
In this study, we define the dual k-Pell, the dual k-Pell-Lucas, and the dual modified k-Pell quaternions and octonions. We investigate some fundamental algebraic properties of these quaternions and octonions. In addition we give Binet's formulae and generating functions.